Evaluating Hunting Success of Pen-Reared and Wild Northern Bobwhite in a Reclaimed Kentucky Mineland - Jeremy P. Orange; John M. Yeiser; Danna L. Baxley; John J. Morgan; Ben A. Robinson (National Quail Symposium Proceedings, 2017)
Northern bobwhites (Colinus virginianus) have experienced severe population declines across their distribution. In order to address population declines and to continue providing hunting opportunities, multi-state efforts have been undertaken to stabilize and restore bobwhite populations. Ongoing efforts using the National Bobwhite Conservation Initiative’s quail focus area approach have so far demonstrated success throughout Kentucky. However, population increases in the Peabody Bobwhite Focal Area, in western Kentucky, have not been correlated to increases in perceived hunter success. Consequently, some sportsmen question the effectiveness of focal area conservation. In response to hunter concerns, we tested dog hunting ability with wild and pen-reared bobwhites. We also measured evasive behaviors of wild bobwhite using radiotelemetry. During the 2013–2014 and 2014–2015 hunting seasons we conducted 114 dog trials. Dogs detected bobwhite during 46 of 59 (78.0%) pen-reared trials and 16 of 55 (29.1%) wild bird trials. When dogs did not detect wild quail, birds ran away 64.1% of the time and remained motionless 20.5% of the time. Using an information-theoretic approach, we determined that bird type (wild vs. pen-reared) had a significant effect on bird detection, with dogs 8.62 times more likely to detect pen-reared birds than wild birds. We recommend that hunters be informed about differences in dog detection rates between pen-reared and wild bobwhite so that public support needed for wild bobwhite restoration can persist.
Keywords: colinus virginianus; northern bobwhite; dog trial; hunter success; Kentucky; pen-reared